Territorial Cooperation and socio-economic development in the Old EU , New EU and Non EU - Lefteris Topaloglou; Victor Cupcea; Dimitris Kallioras; Panagiotis Pantazis (European Regional Science Association (ERSA), 2012)
Territorial cooperation, taken as collaboration "beyond national boundaries", among administrative bodies and/or political actors, generally offers the ground for functional cooperation towards problem-solving and challenge-tackling, along with the exploitation of the local and regional potentials. In the EU, given the high-level of political integration amongst the Member States, numerous rules and structures have been created to support territorial cooperation. In this context, the territorial cooperation is commonly linked to `top-down' policy initiatives, most notably in INTERREG. The Europe 2020 strategy is linked to transnational territorial cooperation, especially through its third objective, aiming at inclusive growth and thereby contributing to the objective of territorial cohesion. The main aim of this essay is to examine the types, domains, driving forces and added value of territorial cooperation which occurs in EU and its neighboring regions. The paper attempts to shed some light upon the final results derived from a Computer-Assisted Web Interviewing (CAWI), one of the main research tools of the TERCO Project, which stands for 'European Territorial Cooperation as a Factor of Growth, Jobs and Quality of Life', an ESPON Applied Research project under Priority 1 (2013/1/9). The survey, is based upon the empirical results derived from the fieldwork conducted in nine (9) Case Studies, along nineteen (19) countries classified in three groups (Old MS, New MS and Non MS), and three (3) non Europe countries (Morocco, Argentina and Uruguay). The findings of the analysis provide valuable information from a scientific and policy making angle.
Keywords: F10; F20; H70; O10; O19; O20; O40; 330; territorial cooperation; Twinning; INTERREG; development; growth; jobs